Farnesol Has an Anti-obesity Effect in High-Fat Diet-Induced Obese Mice and Induces the Development of Beige Adipocytes in Human Adipose Tissue Derived-Mesenchymal Stem Cells - Kim, Hye-Lin; Jung, Yunu; Park, Jinbong; Youn, Dong-Hyun; Kang, JongWook; Lim, Seona; Lee, Beom Su; Jeong, Mi-Young; Choe, Seong-Kyu; Park, Raekil; Ahn, Kwang Seok; Um, Jae-Young (Frontiers in Pharmacology, 2017)
Brown adipocytes dissipate energy as heat and hence have an important therapeutic capacity for obesity. Development of brown-like adipocytes (also called beige) is also another attractive target for obesity treatment. Here, we investigated the effect of farnesol, an isoprenoid, on adipogenesis in adipocytes and on the browning of white adipose tissue as well as on the weight gain of high-fat diet (HFD)-induced obese mice. Farnesol inhibited adipogenesis and the related key regulators including peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα) through the up-regulation of AMP-activated protein kinase (AMPK) in 3T3-L1 murine adipocytes and human adipose tissue-derived mesenchymal stem cells (hAMSCs). Farnesol markedly increased the expression of uncoupling protein 1 (UCP1) and peroxisome proliferator-activated receptor γ coactivator 1 α (PGC1α) in white adipocytes differentiated from hAMSCs. In addition, farnesol limited the weight gain in HFD obese mice and induced the development of beige adipocytes in both inguinal and epididymal white adipose tissue. These results suggest that farnesol could be a potential therapeutic agent for obesity treatment.